Genetic stability of an Escherichia coli strain engineered to produce a novel therapeutic DNA vaccine encoding chicken type II collagen for rheumatoid arthritis. (January 2017) - Juan, Long; Xiao, Zhao; Fang, Yuan; Fei, Liang; Nan, Liu; Song, Yun; Ling, Wang; Yuying, Sun; Yongzhi, Xi
Graphical abstract: Highlights: A DH5α strain producing CCII DNA vaccine was used to found a three-tier cell bank. Genetic stability of this strain during continue passage and storage was proved. This strain showed a high plasmid preservation and yield after long-term storage. Abstract: The development of therapeutic DNA vaccines capable of recovering immunological tolerance through the induction of both CD4 + CD25 + FoxP3 + regulatory and CD3 + CD8 + C28-suppressor T cells, and/or inhibition of both autoreactive CD4 + CD28+ type 1 T helper and autoantibody-producing B cells offers a promising new strategy for the treatment of rheumatoid arthritis. Previously, we developed pcDNA-CCOL2A1, a novel therapeutic DNA vaccine, which encodes the full-length chicken type II collagen sequence, and demonstrated that the efficacy of this vaccine for treating rheumatoid arthritis was comparable to that of the current "gold standard" treatment, methotrexate. In this study, we investigated the genetic stability of a strain engineered to produce the vaccine during continuous passage and long-term storage at different temperatures. By screening a panel of 12 strains, we identified a DH5α strain that exhibited high levels (12.30 ± 0.05 mg L −1 ) of pcDNA-CCOL2A1 production after 15 h cultivation, and subsequently utilized this strain to establish a three-tier cells bank for future studies. Continuous passage of this strain for 100 inoculation times demonstrated that a higher percentage (>95%) of cells maintained the plasmid when cultivated under selective pressure (ampicillin) than under nonselective conditions, suggesting that the presence of antibiotics in the medium prevents the loss of the pcDNA-CCOL2A1 plasmid. Meanwhile, restriction digestion and gene sequencing analyses demonstrated that the pcDNA-CCOL2A1 vector remained stable, and that the plasmid sequence was conserved during this period. Lastly, the DH5α pcDNA-CCOL2A1 strain exhibited a high plasmid preservation (>90%) and high levels of plasmid production (9.05mg L −1 ) after storage for 60 months at −80 °C. Furthermore the plasmid extracted from the DH5α pcDNA-CCOL2A1 strain after storage for 60 months at −80 °C was transfected to COS-7 cells, it can stably express the target protein chicken type II collagen. Conversely, this strain exhibited a complete loss of capability after 24 and 18 months storage at −20 °C and 4 °C, respectively. These findings will facilitate further pilot-scale testing, and even industrial-scale production, of the novel therapeutic vaccine pcDNA-CCOL2A1.